Recommendations for the Contents of the “Glycan Profile” Part of a Product Specification File - O. A. Vaganova (Регуляторные исследования и экспертиза лекарственных средств)
“Glycan Profile” is a necessary part of manufacturers’ product specification files for monoclonal antibody active ingredients or final products and erythropoietin active ingredients. The expert of the Federal State Budgetary Institution “Scientific Centre for Expert Evaluation of Medicinal Products” of the Ministry of Health of the Russian Federation provides recommendations for a step-by-step presentation of the test procedure, which will allow applicants to align product specification files for Russian- and foreign-produced medicinal products, help experts to minimise or eliminate the need to request additional information from applicants, and will contribute to timely batch release of medicinal products.